Base-promoted nucleophilic fluoroarenes substitution of CF bonds. Issue 2 (11th January 2018) - Su, Ji; Chen, Qian; Lu, Le; Ma, Yuan; Auyoung, George Hong Lok; Hua, Ruimao
Abstract: With the use of KOH/DMSO as the superbase medium, the nucleophilic fluoroarene substitution for CF bonds is presented. The transformation proceeds smoothly with the use of fluoroarenes bearing not only electron-withdrawing group, but also electron-donating group and a variety of nucleophiles such as alcohols, phenols, amines, amides and nitrogen-heterocyclic compounds. The double nucleophilic substitution using ortho -difluoroarenes and nucleophiles bearing ortho -dinucleophilic groups results in the formation of 2, 3-dihydro-1, 4-benzodioxins, dibenzo[b, e][1, 4]dioxins and 10 H -phenoxazines in moderate to good yields. Graphical abstract: